The Effect of Meditation on Blood Pressure in Middle Adult Hypertension Sufferers in the Pandanwangi Community Health Center Area, Malang City - Subekti, Imam; Kartika, Nugrahani Candra; Suyanto, Edy (Journal of Rural Community Nursing Practice, 2024)
Hypertension is the most common chronic disease suffered by people in Indonesia and is the main cause of death every year. Hypertension is called the silent killer because it is often experienced without complaints, and causes serious complications, especially in middle adulthood. Management of hypertension can be done with non-pharmacological therapy, one of which is meditation. This study aims to analyze the effect of meditation on reducing blood pressure in middle-aged hypertensive sufferers in the Pandanwangi Health Center working area, Malang City on April 2022. The research design was quasi experimental with a pre-test post-test design with control group. The total sample was 42 respondents divided into two groups (treatment and control). Statistical analysis uses the Mann Whitney test. The results showed that there was a decrease in the average systolic blood pressure from 148.33 mmHg to 139.28 mmHg and diastolic blood pressure from 89.04 mmHg to 83.57 mmHg in the treatment group after being given meditation for 3 sessions. The statistical test results show that the p-value for measuring post-treatment systolic blood pressure between the treatment group and the control group is 0.022 ≤ alpha 0.05, and the p-value for measuring post-treatment diastolic between the treatment group and the control group is 0.005 ≤ alpha 0.05. So, it can be concluded that there is an effect of meditation on reducing blood pressure in middle-aged hypertensive sufferers. It is hoped that in future research can be continued on the effect of meditation on blood pressure in other age groups (elderly age) by analyzing factors that can influence blood pressure, such as stress, physical activity and sleep patterns.